Reviving DIY: The importance of do it yourself to the Portuguese alternative rock scene59 - Oliveira, A. (2016)
The approach of DIY music careers lies in the premise that music is a unifying pole of activities, clustering a diversity of practices and lifestyles around it. The analysis of musical production is usually based on an entrepreneurial perspective about creative workers and, specifically, about the musicians. In this context, it can be useful to revisit one of the core values of the punk subculture, the DIY ethos, based on empowerment, on taking possession of the means of production, as an alternative to mainstream production circuits. Starting from the case of three projects - Filho Unico, Haus and Hey, Pachuco! - we explore the relevance of do it yourself logics and procedures in the construction and maintenance of musical careers in the alternative rock, considering their impact on Lisbon metropolitan area's music alternative scenes.